2011
DOI: 10.1055/s-0030-1256520
|View full text |Cite
|
Sign up to set email alerts
|

Dysphagia caused by migrated mesh after paraesophageal hernia repair

Abstract: UCTN-Unusual cases and technical notes E257 Arroyo Q et al. Dysphagia caused by migrated mesh after paraesophageal hernia repair … Endoscopy 2011; 43: E257-E258 This document was downloaded for personal use only. Unauthorized distribution is strictly prohibited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Two prospective, randomized clinical trials have shown that "tension-free" laparoscopic hernia repair with prosthetic graft prevents recurrence [5,6]. However, use of synthetic materials for crural reinforcement produced potentially serious problems, such as erosion and dysphagia [6][7][8][9]. This leads to popularization of biological grafts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two prospective, randomized clinical trials have shown that "tension-free" laparoscopic hernia repair with prosthetic graft prevents recurrence [5,6]. However, use of synthetic materials for crural reinforcement produced potentially serious problems, such as erosion and dysphagia [6][7][8][9]. This leads to popularization of biological grafts.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown higher recurrence rates after a suture-based repair of hiatal hernias [2][3][4]. A "tension-free" repair with prosthetic mesh allowed decreasing recurrence [5], but the use of synthetic materials produced potentially serious problems, such as erosion and dysphagia [6][7][8][9]. Multiple reports showed reduction in short-term recurrence rate after hiatal hernia repair with biologic grafts [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Closure with mesh typically is reserved for situations where the defect is too large to be closed primarily. Concerns regarding the routine use of mesh include the potential for mesh erosion into the stomach or esophagus, esophageal stricture formation, mesh migration, and infection [16, 17]. Most surgeons have abandoned the use of nonabsorbable mesh at the esophageal hiatus for these reasons [15].…”
Section: Discussionmentioning
confidence: 99%
“…There were no graft related complications, such as erosion and stricture formation as can be seen with permanent prosthetic meshes. [16][17][18][19] Mesh-related complications is vexing in both biologically derived grafts and prosthetic mesh repairs. Having a graft that is safe to use around the relatively mobile esophagus is comforting.…”
Section: Discussionmentioning
confidence: 99%